Aphrahat's demonstrations : a conversation with the Jews of Mesopotamia - Lizorkin, Ilya (Stellenbosch : University of Stellenbosch, 2009)
Thesis (DPhil (Ancient Studies)--University of Stellenbosch, 2009.